The Impact of High Temperatures on the Strength of Recycled Aggregate Concrete - Kamal Ibtisam; Ali Abed Ammar (E3S Web of Conferences)
The recent study share out the fabrication of Recycled Aggregate Concrete (RAC) and studying the influence of exposure to high temperatures on the density and compressive strength. RAC mixes were prepared using (1: 2: 4) cement: sand: coarse aggregate (recycled aggregate 50 wt%.), water/cement (0.5). RAC cubes of 150mm x 150mm x 150mm were cast and appropriately cured for 28 days according to standard procedure. The impact of elevated temperature on the compressive strength and density of RACs was investigated using an adopted central composite design of two factorials (temperature: 69.3-210.7oC and heating time: 4.7-6.8 h) based on Response Surface Methodology. An optimum of 32.48 % and 3.09 % reduction in average compressive strength and density respectively were estimated from ANOVA analysis when exposed to an optimum temperature of 217.7oC and heating time of 6.8 hours. The mathematical models presenting the impact of high temperature on the investigated characteristics were estimated and validated. For design considerations, it is very necessary to have information about the RACs fabricated as construction materials before their utilization as structural elements. Also, the exploration into the high-temperature performance of RACs is vital to the conservation of life and economics in fire crises.